2017
DOI: 10.1016/j.foodqual.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The magic water test. An affective paired comparison approach to evaluate taste sensitivity in pre-schoolers

Abstract: Children in pre-school age present a limited cognitive development, a restricted vocabulary and a short attention span, which do not allow conducting classical taste sensitivity measures as developed for adults. The aim of this study was to develop and validate an age-appropriate protocol for sensitivity testing of the five basic tastes with pre-schoolers. One hundred and forty children aged 3–4 years (mean age 46.3 months, SD 3.4) performed a paired comparison task consisting of discriminating water from ‘‘ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 154 publications
(249 reference statements)
0
7
0
Order By: Relevance
“…The task was to discriminate consistently between the two samples within the pair. For the complete protocol and set-up of the sensitivity-testing, see Vennerød et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The task was to discriminate consistently between the two samples within the pair. For the complete protocol and set-up of the sensitivity-testing, see Vennerød et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The PROP taste sensitivity test will take approximately 12-15 min per child. It is a safe, simple, non-invasive test to examine individual's perception to bitter taste [14], extensively used in adults and children as young as 3 years of age [39] and been recommended for bitter taste sensitivity screening at an epidemiological level [14,24]. Children will rinse and spit out 7 solutions containing increasing levels of PROP concentrations (ranging from 17-3200 uMol/L) (referred to as PROP taste solutions).…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous research has highlighted that children show a better discrimination ability when analytical methods are framed as hedonic tasks due to their lower cognitive demand (Liem et al, 2004b; Vennerød et al, 2017). For instance, ranking tests and paired comparisons framed as hedonic tasks have been successfully applied with children (Cordelle et al, 2005; Laureati et al, 2016; Léon et al, 1999; Vennerød et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has highlighted that children show a better discrimination ability when analytical methods are framed as hedonic tasks due to their lower cognitive demand (Liem et al, 2004b; Vennerød et al, 2017). For instance, ranking tests and paired comparisons framed as hedonic tasks have been successfully applied with children (Cordelle et al, 2005; Laureati et al, 2016; Léon et al, 1999; Vennerød et al, 2017). In addition, Lima et al (2018) has recently reported that school‐age children showed a higher hedonic sensitivity toward sugar reduction than adults despite their lower ability to detect differences in their sensory characteristics using a check‐all‐that‐apply question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation